Programa de Modernização da Gestão Pública/ metas para a educação/ 2007-2010: análise sobre a Gestão Democrática da educação de Pernambuco - Cavalcanti, Ana Claudia Dantas (2011)
The focus of our study is the Education Management Modernization Program of the Government of Pernambuco, in the period 2007 to 2010.The study gives special attention to the assessment of the policies and the design of the democratic management mechanisms established by the .program. The research question was : Is the: PMG / ME seen as an educational policy that contributes for strengthening or weakening the democratic management of education in Pernambuco? Our overall objective was to analyze the process by which the democratic school management strategies were established in the above period. Considering this major objective, other specific aspects of the program were analyzed such as :( i) the implementation process of the PMG / ME and its impact on school management strategies in the stateoperated schools ; ( ii) the identification of actions of the PMG / ME that aimed at establishing democratic management of education; and (iii) the assessment of how the PMG / ME could contributed to strengthening or weakening the democratic management of education in the state. The study used a qualitative methodology supported by questionnaires for data collection. The following categories of analysis were selected: State, Democracy and Public Policy. The State is understood as the establishment of relationships of power within the society Foucault (1979). Public Policies are ¨ the State in action¨ as defined by Melo on (2002) following Jobert & Muller (1989). The concept of democracy implies the control exercised by the society and the division of power. Following the concepts mentioned before, participatory democracy leads to actions of the State and the society by the exercise of their micropowers as advocated by Foucault, and consequently the participatory democracy establishes forms of power and resistance. Power can be established/re-established by the State or society. The one who has the power can counteract through resistance. The research was supported by strong national and international literature, including contributions from Foucault (1979, 1987, 2000, 2001, 2003, 2004, 2006 and 2008) and Bakhtin (2000, 2002). In addition, the methodology of qualitative/documentary research (Ludke and Andre, 1986) was used to analyze the process of democratic construction im PMG/ME. The implementation of the PMG/ME was characterized by continuity of government policies, initially adopted under the Administrative Reform of the State in 1995 and subsequently developed in the Administration os Eduardo Campos (2007 to 2010). This Administration intended to strengthen the State management through the PNAGE/PE. This study concluded that the actions developed by the PMG/ME have no impact in the development of democratic management in the state-operated schools because there were no specific mechanisms or instruments to strength the exercise of this type of management at the school level.